Heterostructures impacting deformation strengthening processes in QP steels: Investigating the interplay of grain rotation, slip transfer, and back stress strengthening - Yao Zhou; Weijie Wu; Jinxu Li (Journal of Materials Research and Technology, 2024)
QP (Quenching and Partitioning) steel, the third generation of advanced high-strength steel, has garnered significant attention due to its exceptional mechanical performance. This paper investigates the interplay of grain rotation, slip transfer, and back stress strengthening through quasi in-situ deformation scanning electron microscope (SEM), electron backscatter diffraction (EBSD), and load-unload-reload (LUR) cycle tests. The findings reveal the substantial differences between QP980 and QP1180. QP980, characterized by heterostructures, exhibits non-uniform deformation characteristics. In regions with heterostructures, grain rotation inhibits slip transfer, leading to the accumulation of geometrically necessary dislocations (GNDs) and the formation of dislocation substructures (walls and cells), resulting in significant back stress strengthening. Conversely, due to the lack of heterogeneous structural regions, QP1180 displays uniform deformation characteristics, grain rotation and slip transfer promote each other, showing a weaker and different back stress strengthening compared to QP980. The interplay of grain rotation, slip transmission, and dislocation substructure formation influences the back stress behavior, impacting the mechanical properties and deformation behavior of the materials. This research provides a novel perspective on plastic deformation and strengthening theory, and serves as a valuable reference for material design and performance optimization.